Research on the Microstructure, Mechanical Properties and Strengthening Mechanism of Nanocrystalline Al-Mo Alloy Films - Ying Wang; Huanqing Xu; Yulan Chen; Xiaoben Qi; Ning Zhong (Nanomaterials)
In this work, the Al-Mo nanocrystalline alloy films with Mo contents ranging from 0–10.5 at.% were prepared via magnetron co-sputtering technology. The composition and microstructure of alloy thin films were studied using XRD, TEM, and EDS. The mechanical behaviors were tested through nanoindentation. The weights of each strengthening factor were calculated and the strengthening mechanism of alloy thin films was revealed. The results indicate that a portion of Mo atoms exist in the Al lattice, forming a solid solution of Mo in Al. The other part of Mo atoms tends to segregate at the grain boundaries, and this segregation becomes more pronounced with an increase in Mo content. There are no compounds or second phases present in any alloy films. As the Mo element content increases, the grain size of the alloy films gradually decreases. The hardness of pure aluminum film is 2.2 GPa. The hardness increases with an increase in Mo content. When the Mo content is 10.5 at.%, The hardness of the film increases to a maximum value of 4.9 GPa. The fine grain (<semantics>∆Hgb</semantics>), solid solution (<semantics>∆Hss</semantics>), and nanocrystalline solute pinning (<semantics>∆Hnc,ss</semantics>) are the three main reasons for the increase in the hardness of alloy thin films. The contribution of <semantics>∆Hgb</semantics> is the largest, accounting for over 60% of the total, while the contribution of <semantics>∆Hss</semantics> accounts for about 30%, ranking second. The rest of the increase is due to <semantics>∆Hnc,ss</semantics>.